Effects of hip flexor training on sprint, shuttle run, and vertical jump performance - Deane, R. S.; Chow, J. W.; Tillman, M. D.; Fournier, K. A. (The Journal of Strength and Conditioning Research, 2005)
Although hip flexion is integral in sports, hip flexion exercises are seldom emphasized in strength and conditioning for sports performance. This study aimed to determine whether a hip flexor resistance-training program could improve performance on a variety of tasks. Thirteen men and 11 women completed an 8-week hip flexion resistance-training program. Eleven men and 13 women served as controls. Isometric hip flexion strength, 40-yd dash time and the time for the first 10-yds, 4 x 5.8-m shuttle run time, and vertical jump height were evaluated at the beginning and end of the training and control period. Improvements were observed in the training group but not in the control group. Individuals in the training group improved hip flexion strength by 12.2% and decreased their 40-yd and shuttle run times by 3.8% and 9.0%, respectively. An increase in hip flexion strength can help to improve sprint and agility performance for physically active, untrained individuals.